Migrating histories of art : self-translations of a discipline - Costa, Maria Teresa, 1979-; Hönes, Hans Christian (Studien aus dem Warburg-Haus ;, 2018)
"Art historians have been facing the challenge - even from before the advent of globalization - of writing for an international audience and translating their own work into a foreign language - whether forced by exile, voluntary migration, or simply in order to reach wider audiences. Migrating Histories of Art aims to study the biographical and academic impact of these self-translations, and how the adoption and processing of foreign-language texts and their corresponding methodologies have been fundamental to the disciplinary discourse of art history. While often creating distinctly "multifaceted" personal biographies and establishing an international disciplinary discourse, self-translation also fosters the creation of instances of linguistic and methodological hegemony"--